Prediction of Discharge Disposition in Geriatric Women after Traumatic Injury - Jon, Dorfman; Allison, Wyman; Gordon, FitzGerald; Brandon, Colvin; Timothy, A. Emhoff; Frederick, A. Anderson; Heena, P. Santry (Journal of Aging Research And Healthcare, 2017)
Background: Discharge disposition planning begins at admission and is frequently one of the first questions posed to healthcare providers by patients and families. We hypothesized that pre-injury functional status would predict discharge disposition. Methods: We linked prospective data from the Worcester, MA cohort of the Global Longitudinal Study of Osteoporosis (GLOW) study and the UMassMemorial Level 1 Trauma Center Registry to determine predictors of discharge disposition for female geriatric (over the age of 55) trauma patients using bivariate comparisons and multivariable modeling. Results: 154 women of 5,091 in the Worcester GLOW cohort were evaluated for traumatic injury at UMassMemorial and were discharged alive either to their home (n=30) or to rehabilitation, skilled nursing, or nursing home facilities (n=124). The mean age was 79 years and the majority (99%) was white. There were no statistically significant differences in comorbidities or injury severity score between the groups. All women with femur fractures were discharged to a facility. The most common injury among women discharged home was traumatic brain injury. While univariate analysis revealed differences in pre-injury activity status, only age remained statistically different in a logistic regression model predicting discharge to facility (OR 2.61 per additional 10 years of age, 95% CI 1.62 to 4.19, p<0.0001). Conclusions: The majority of elderly women are not discharged home after injury. Pre-injury activity status was not associated with discharge disposition when accounting for other factors. It appears that physical function, which deteriorates with age, is a proxy for aging in older women at risk for osteoporosis.
Keywords: geriatric; trauma; injury; frailty; disposition